A practice‐based evidence investigation of God representations in spiritually integrated psychotherapies. Issue 4 (24th October 2020) - Currier, Joseph M.; McDermott, Ryon C.; Stevens, Laura T.; Isaak, Steven L.; Davis, Edward B.; Hollingsworth, William‐Glenn L.; Archer, Glenn D.; Stefurak, Tres
Abstract: Objective: This practice‐based evidence study examined trajectories of God representations and psychological distress among Christians participating in spiritually integrated psychotherapies (SIPs). Methods: In total, 17 clinicians practicing SIPs in a mid‐sized city on the US Gulf Coast implemented session‐to‐session assessments of these outcomes with 158 clients over a 4‐month period and also reported their use of specific spiritual interventions after each session (e.g., affirmed client's divine worth). Results: Multivariate growth modeling revealed clients' psychological distress decreased over the study period whereas authoritarian God representations increased and benevolent God representations remained stable. In addition, clients who increased in benevolent representations of God had a greater likelihood of experiencing alleviation of psychological distress. Conclusion: These findings affirm the potential efficacy of SIPs and cultural importance of belief in a benevolent deity as a source of strength, identity, and potential healing among Christians clients who prefer a spiritually integrated approach in psychotherapy.